RNA Virus Diversity in Birds and Small Mammals From Qinghai–Tibet Plateau of China - Zhu, Wentao; Yang, Jing; Lu, Shan; Jin, Dong; Pu, Ji; Wu, Shusheng; Luo, Xue-Lian; Liu, Liyun; Li, Zhenjun; Xu, Jianguo (Frontiers in Microbiology, 2022)
Most emerging and re-emerging viruses causing infectious diseases in humans and domestic animals have originated from wildlife. However, current knowledge of the spectrum of RNA viruses in the Qinghai–Tibet Plateau in China is still limited. Here, we performed metatranscriptomic sequencing on fecal samples from 56 birds and 91 small mammals in Tibet and Qinghai Provinces, China, to delineate their viromes and focused on vertebrate RNA viruses. A total of 184 nearly complete genome RNA viruses belonging to 28 families were identified. Among these, 173 new viruses shared <90% amino acid identity with previously known viral sequences. Several of these viruses, such as those belonging to genera Orthonairovirus and Hepatovirus, could be zoonotic viruses. In addition, host taxonomy and geographical location of these viruses showed new hosts and distribution of several previously discovered viruses. Moreover, 12 invertebrate RNA viruses were identified with <40% amino acid identity to known viruses, indicating that they belong to potentially new taxa. The detection and characterization of RNA viruses from wildlife will broaden our knowledge of virus biodiversity and possible viral diseases in the Qinghai–Tibet Plateau.